Leitura filosófica como proposta para o uso de textos clássicos nas aulas de filosofia no ensino médio - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá)
This work deals with the philosophical reading as a proposal to work, with the classes of Philosophy of High School, the classic texts. The approach to Philosophy Teaching in High School begins by going through the periods where discipline was present and when it was withdrawn from the school curriculum. It is emphasized that Philosophy is a discipline of thought and that has the characteristic of being an activity of creating concepts. Thus, the lesson needs to escape the content models that simply talk about History of Philosophy. This is a challenging context for the teacher, however, should be something in the day to day activities of teaching. The reading of a classic in the school context makes the student understand the purpose of Philosophy in High School. Thus what is expected with the work is to present the philosophical reading as a methodology to work classical texts in the classroom and, with this, to enable the student to have contact with the history of Philosophy, and not only that, from reading philosophical to be able to reflect on the subject in question, conceptualize, apprehend the philosophical concepts, and then problematize and present his understanding on the subject, constructing his philosophy.
Keywords: Filosofia - Estudo e ensino; Textos clássicos; Leitura filosófica